Analysis of the Implementation of Holistic Education to Form Disciplined Characters in Students of Sahabat Alam Elementary School, Palangka Raya City - Zainab, Siti; Bulkani, Bulkani (Institute For Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Backgorund: Holistic education is an educational method to build humans as a whole by developing their potential which includes social-emotional potential, intellectual potential, moral or character potential as well as creativity and spirituality. Aim: The purpose of this study is to analyze the implementation of holistic education that forms disciplinary character in students of Elementary School Sahabat Alam Palangka Raya city. Method: This research uses a descriptive qualitative approach with a case study method. Result and Discussions: Based on the results of the research, the implementation of holistic education at Elementary School Sahabat Alam Palangka Raya aims to form a disciplinary character in students that has been well implemented in the learning process, and emphasizes the active involvement of all parties in the disciplinary process. This approach involves intellectual, emotional, physical, social, aesthetic, and spiritual aspects. Success is achieved through various strategies, including thorough planning, collaboration with parents, use of role play methods, involving learners in rule making, consistent monitoring and evaluation, and positive interventions. Conclusions: The holistic approach in this school does not aim to homogenize learners, but to optimize individual development according to their interests and talents. And the application of appropriate strategies can effectively shape learners' disciplinary character, while creating a safe and positive learning environment.